Antipodes In Search of the Southern Continent - Stallard, Avan Judd (Australian History, 2016)
This book is a new history of an ancient geography. It reassesses the evidence for why Europeans believed a massive southern continent existed, and why they advocated for its discovery. When ships were equal to ambitions, explorers set out to find and claim Terra Australis. Antipodes charts these voyages-voyages both through the imagination and across the High Seas-in pursuit of the mythical Terra Australis. In doing so, the question is asked: how could so many fail to see the realities they encountered? And how is it a mythical land held the gaze of an era famed for breaking free the shackles of superstition? That Terra Australis did not exist didn't stop explorers pursuing the continent, unwilling to abandon the promise of such a rich and magnificent land till it was stripped of every ounce of value it had ever promised. In the process, the southern continent-an imaginary land-became one of the shaping forces of early modern history. Includes 48 pages of b&w and colour images.